Development of Novel Bienzymatic Assay for Quantification of Glucose inHuman Serum - Mantelingu, K. R. C. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The main objective of this investigation was to design and to develop a simple, sensitive, and convenient assay for quantification of glucose in human serum sample. Materials and Methods: A novel bienzymatic assay for the quantification of glucose by spectrophotometry has been developed. The method is based on the coupling of 4-aminoantipyrine and iminodibenzyl in the presence of bienzyme peroxidase/glucose oxidase (GOx) to form a blue colored product which is monitored for absorbance at 620 nm at 23°C in 100 mmol/L KH2PO4/NaOH buffer of pH 6.3. Results and Discussion: Under optimized assay conditions, glucose could be quantified in a linear range from 1.15 to 562 μmol/L and 2.31 to 370 μmol/L by kinetic and fixed time method. The limit of detection and limit of quantification were measured. Michaelis–Menten constant for glucose was found to Km = 357 μmol/L and maximum rate of the reaction (Vmax) was 0.117 × 10−6 mol/L/min. The proposed method was applied for the quantification of glucose in human serum samples, which has a good regression coefficient of 0.9992 with the enzymatic kit method. The inter-day precision was 0.53-2.9% (n = 10) and intra-day precision was 1.5-3.03% (n = 10). The accuracy range for glucose was fond to be 90-104%. The glucose recovery ranged from 91.92% to 108.5%. Conclusion: The present assay was rapid, sensitive, and convenient for quantification of glucose in human serum sample with good recovery, high accuracy, and minimum interference.